Produtividade de soja in sílico no bioma Cerrado em função do fenômeno El Niño Oscilação Sul - Nicolau Neto, Publius Lentulus Artiaga (2023)
Soybean complex has stood out in the growth of the Brazilian economy. One factor that has contributed to this success in production is agroclimate risk zoning, which recommend sowing dates and areas for Brazil with lower climate risk. In this context, during the growing season, crop is subject to water stresses and higher oscillations of air temperature, which result in a decrease in yield and grain quality. Climatic events such as El Niño Southern Oscillation (ENSO) cause serious social and economic impacts, and are characterized with events of floods, storms, frosts and prolonged droughts. Crop and environment has a multiple interactions and crop modeling comes as a science based on a simple representation of a system capable of represent these interactions. This way, the aim of this study was to evaluate the effects of the ENOS on simulated soybean yield in different Brazilian regions, sowing dates, maturation groups and soil type. For this, the CSM-CROPGRO-Soybean model was used to simulate yield for 14 locations in Brazil. Climatic data from 1961 to 2016 was obtained from the National Institute of Meteorology and complemented from NASAPOWER until 2020, totaling 60 growing seasons of simulation. The simulation were performed using three soil types and three maturation groups, obtained from works that carried out the calibration of the model. Sowing dates were based on agroclimatic risk zoning, considering the maximum sowing window, divided into each ten days. The yield was correlated with the qualitative classification of ENOS (El Niño, La Niña and neutral phase). El Niño and La Niña phase occurred in 35% of growing season each, totaling 42 events in 60 years. In Cerrado biome, the majority of municipalities indicating a better performance with a late cycle, considering the greater sowing window. The greatest yield gains were obtained in growing seasons with neutral and La Niña phase, resulting in higher yield when compared to El Niño phase. This way, the sowing dates and crop cycle can help to reduce climate risk, independent of ENOS phase, but with soybean showing higher potential yield in growing seasons under neutral and La Niña.